THE USE OF CRITICAL DISCOURSE ANALYSIS APPROACHES ON ENGLISH TEXTBOOK STUDIES FOR ENGLISH LANGUAGE TEACHING: A SYSTEMATIC LITERATURE REVIEW FROM 2012 TO 2021 - Yasir Mubarok; Astri Dwi Floranti; Wawan Gunawan (Epigram, 2026)
While scholars have widely acknowledged the value of integrating Critical Discourse Analysis (CDA) into educational research as a means of understanding the relationship between pedagogical practices and social contexts, this study presents a decade-long systematic literature review of English textbook studies conducted within the CDA framework in the field of English Language Teaching (ELT). The data comprised 41 journal articles published between 2012 and 2021, which were retrieved using the Publish or Perish (PoP) software and analyzed through an open-coding approach. The findings reveal a gradual increase in publication trends, particularly from 2018 onward. The reviewed studies were predominantly conducted in expanding-circle countries, with Indonesia and Iran emerging as the most frequently represented contexts. Consequently, a large proportion of the research focused on English textbooks used at the upper secondary education level. Gender inequality and its representation emerged as the most extensively examined topic. Other prominent research themes included ideology construction, educational values, racism, identity and citizenship, multimodality, and CDA-based textbook evaluation. Finally, this study contributes to the advancement of the CDA framework in English textbook research and offers directions for future studies in this field.